Confidential enquiry into maternal deaths in the Netherlands, 2006–2018 - Athanasios F. Kallianidis; Joke M. Schutte; Louise E. M. Schuringa; Ingrid C. M. Beenakkers; Kitty W. M. Bloemenkamp; Babette A. M. Braams‐Lisman; Jerome Cornette; Simone M. Kuppens; Anna L. Rietveld; Timme Schaap; Jelle Stekelenburg; Joost J. Zwart; et al. (Acta Obstetricia et Gynecologica Scandinavica)
Abstract Introduction To calculate the maternal mortality ratio (MMR) for 2006–2018 in the Netherlands and compare this with 1993–2005, and to describe women’s characteristics, causes of death and improvable factors. Material and Methods We performed a nationwide, cohort study of all maternal deaths between January 1, 2006 and December 31, 2018 reported to the Audit Committee Maternal Mortality and Morbidity. Main outcome measures were the national MMR and causes of death. Results Overall MMR was 6.2 per 100 000 live births, a decrease from 12.1 in 1993–2005 (risk ratio [RR] 0.5). Women with a non‐western ethnic background had an increased MMR compared with Dutch women (MMR 6.5 vs. 5.0, RR 1.3). The MMR was increased among women with a background from Surinam/Dutch Antilles (MMR 14.7, RR 2.9). Half of all women had an uncomplicated medical history (79/161, 49.1%). Of 171 pregnancy‐related deaths within 1 year postpartum, 102 (60%) had a direct and 69 (40%) an indirect cause of death. Leading causes within 42 days postpartum were cardiac disease (n = 21, 14.9%), hypertensive disorders (n = 20, 14.2%) and thrombosis (n = 19, 13.5%). Up to 1 year postpartum, the most common cause of death was cardiac disease (n = 32, 18.7%). Improvable care factors were identified in 76 (47.5%) of all deaths. Conclusions Maternal mortality halved in 2006–2018 compared with 1993–2005. Cardiac disease became the main cause. In almost half of all deaths, improvable factors were identified and women with a background from Surinam/Dutch Antilles had a threefold increased risk of death compared with Dutch women without a background of migration.